THE STATUS OF MARKETING AS A MANAGERIAL FUNCTION IN THE LIBYAN FOOD MANUFACTURING INDUSTRY - حودانه بن عيسى (Dirasat in Economics and Business, 1976)
Many authorities in the field of marketing develompent believe that the status given to the marketing management, and the chief marketing executive- reflects the marketing philosophy of the top management in a given business enterprise. This paper is an attempt to determine the way marketing is dealt »,ith, and the relative importance of major marketing facets to the overall marketing strategies in the libyan food manufacturing industry. To this end, twenty one food manufacturing firms in the private sector were investigated. Personal interviews. supported by detailed questionnaire, were used as methods for data collection. All firms investigated were grouped in three different categories according to their stages of marketing organizations. In other B ords. firms were classified as follows: LEVEL ONE : firms without any marketing organisations and marketing activities handled by non-specialists at different levels of the firm organisation LEVEL TWC) : firms with sales departments where the marketing activities are practiced: LEVEL THREE : firms full marketing departments, where the sales department is only a division within the marketing department. The three-level-approach to classifying firms in terms of their marketing organisations, proved to be adequate. in the sense that it showed the extent to which marketing is recognised as a specialised managerial function in its own right.